A new safranin based three-component photoinitiating system for high resolution and low shrinkage printed parts via digital light processing. Issue 68 (9th December 2019) - Nejadebrahim, Atefeh; Ebrahimi, Morteza; Allonas, Xavier; Croutxé-Barghorn, Céline; Ley, Christian; Métral, Boris
Abstract : The resolution and shrinkage of DLP 3D printed parts improve remarkably when SFH + /RSH/IOD + is used as a photoinitiating system. Abstract : Additive manufacturing or 3D printing has attracted the interest of researchers in industry and academia because of its outstanding features. In this study, a new three-component photoinitiating system (PIS) consisting of safranin O (SFH + ), thiol derivatives and diphenyl iodonium salt was used for the free radical photopolymerization of a diacrylate monomer (SR349) in DLP 3D printing. The photoinitiating characteristics of this PIS were evaluated and advantageously compared to those of a conventional PI (TPO) by using RT-FTIR. It is shown that the proposed PIS could be used as an efficient PIS for free radical photopolymerization. In addition, the resolution and shrinkage of printed parts in the presence of this three-component PIS were measured and compared to those printed using TPO as a photoinitiator. The resolution of printed parts was determined by using SEM and profilometry techniques. In addition, photorheometry was used to evaluate the linear shrinkage of samples. Moreover, the initiating mechanism of the three-component PIS was studied by using laser flash photolysis (LFP). A photocyclic mechanism was outlined for the three-component PIS which demonstrated this mechanism would be very beneficial for DLP 3D printing.